Contextual Teaching and Learning with Video Media Effects on Creativity and Learning Outcomes - Mutiara Fatimah; Ismira Ismira; Hafiz Hidayat (Journal of Education Research, 2026)
Traditional instructional approaches in elementary education often fail to contextualize learning within students' real-world experiences, resulting in diminished engagement and limited creative development. This study aimed to examine the effects of Contextual Teaching and Learning (CTL) integrated with video media on the creativity and learning outcomes of fifth-grade students at Sekolah Dasar Negeri 200/III Pondok Beringin. A quantitative experimental design was employed, utilizing a pretest-posttest control group structure. The research sample consisted of all fifth-grade students selected through total sampling, with one class assigned as the experimental group and one class as the control group. Data were gathered through a validated learning outcome test and a student creativity questionnaire, both developed based on established dimensions of creative thinking. Statistical analyses using independent samples t-tests and analysis of covariance revealed that the experimental group exposed to CTL with video media demonstrated significantly higher posttest creativity scores and academic learning outcomes compared to the control group. These findings suggest that contextualizing instruction through real-world connections and dynamic visual media substantially enhances both creative thinking and academic achievement among elementary school students, underscoring the importance of integrating contextual and multimedia-based strategies in elementary education.